Diversity of Mosses and Ferns in Dlundung Waterfall, Mojokerto - Angella Ananda Syaputra; Lailatus Fitri; Badriatul Musyarofah; Nynda Ayu nadira Savitri; Aji Naufal Syafiq; Rofiatun solekha (BEST Journal (Biology Education, Sains and Technology), 2023)
Ferns (Pteridophyta) and mosses (Bryophyta) live in moist areas (hygrophytes) both epiphytes (attached to trees, wood, rocks) and terrestrial (soil). Data about the types of ferns and mosses are very important to know either as a biodiversity database or as a medium to support the learning process. Even the rate of species extinction due to human activities has now reached an alarming level. The aims of this research are to; knowing the types of mosses and ferns found in Dlundung Waterfall, Mojokerto and knowing the level of diversity of mosses in Dlundung Waterfall, Mojokerto. The research design obtain with 3 location to field data, using the roaming method. The results obtained 5 species of mosses (Hyophila apiculata, Ectropothecium falciforme, Dumortiera hirsuta, Orthorrhychium phyllogonioides, Cyathodium Smaragdinum) and 5 species of ferns (Pteris vittata, Adiantum concinnum, Aspelenium nidus, D. canariensis, Cyathea sp.) 5 Types of mosses were identified to the species level, five types of ferns were identified to the genus level.